A move in the right direction: Tracking the traceability of British Thoroughbreds outside of racing - Jane Michelle Williams; Saranna Jordan; Laura Friend; Emily Kay; Matilda Edmunds; Helena Flynn; Stephen Wensley (PLoS ONE, 2025)
Horse welfare within/after racing is often questioned by the public. British Racing’s Horse Welfare Board’s “A life well-lived” strategy provides a blueprint for Thoroughbred welfare, advocating accurate lifetime traceability of horses as essential to achieve this. The Census aimed to establish a population density model for British Thoroughbreds, not actively engaged in racing. Equestrians who owned/kept a Thoroughbred were asked to complete the Census between May and December 2023. Frequency analysis identified patterns in passport compliance, knowledge and understanding of current systems, and profiled Thoroughbred demographics: age, use, and history. Records for 8,256 horses were analysed (margin of error: ± 1%, 99% CI); 98% of horses had a passport, but only 64% were in their current owner’s name despite 90% being aware that they should have changed the horse’s registration details. Horses were predominately owned (91%), were geldings (74%), and aged between 5–14 years (63%); Leisure riding, hacking, and unaffiliated competition were the most common activities participated in; no significant differences in registration compliance occurred between activities. The Census provides an accurate representation of British Thoroughbreds not actively involved in racing totalling 33,600 horses, with 80% traceable. The results offer an insight into owner/keeper decision-making with respect to horse registration and Thoroughbred usage after racing. A need to improve current equine traceability systems through digitalisation and simplification was voiced, alongside enhanced communication strategies to showcase why compliance is important. Ongoing accurate records are essential to support education, research, and strategy to safeguard Thoroughbred welfare across their racing and second careers.